A transparent photo-responsive organogel based on a glycoluril supergelator - Tiefenbacher, Konrad; Dube, Henry; Ajami, Dariush; Rebek, Julius (Chemical Communications, 2011)
The synthesis of an azo-benzene glycoluril supergelator is reported. The control over the gel/sol state can be accomplished by irradiation and heat, but also (in a unidirectional sense) by incorporation of the glycoluril into a more stable supramolecular assembly. © 2011 The Royal Society of Chemistry.
CRIS-Team Scopus Importer:2020-04-02